Impact of a screening protocol for blood pressure level for hypertension in the Korean community health survey. (2nd November 2021) - Shin, Jinho; Kim, Ju-Han; Shin, Jeong Hun; Jung, Mi Hyang; Son, Jung-Woo; Lee, Eun Mi; Kim, Yu Mi; Cho, Jung Sun; Choi, Jung Hyun; Kim, Hack-Lyoung; Lee, Seon Kui; Choi, Sun Hye; et al.
Abstract: Purpose: A community program is an efficient model for improving the management of chronic diseases such as hypertension, diabetes, and dyslipidemia. A specific blood pressure (BP) measurement protocol was developed for community settings in which BP was measured by the interviewer at the interviewee's home. Materials and methods: In the 2018 Korean Community Health Survey, BP was measured twice at a five-minute interval after a five-minute resting period at the beginning of the survey. In 2019, BP was measured at the end of the survey after a two-minute rest and was obtained as three measurements at one-minute intervals. As factors related to BP level, stressful stimuli within 30 min before BP measurement such as smoking, caffeine, and/or exercise; duration of rest; and survey year were analysed. Results: The mean age of participants was 55.2 years, and females accounted for 55.4% of the participants ( n = 399, 838). Stressful stimuli were observed in 21.9% of the participants in 2018 ( n = 188, 440) and 11.3% in 2019 ( n = 211, 398). Duration of rest was 0 min (2.1%), two minutes (55.0%), and five minutes (47.9%). When adjusted for age, sex, body mass index, antihypertensive medication, the arm of measurement, survey year (beta= −4.092), stressful stimuli (beta = 0.834), and resting time (beta = −1.296 per one minute of rest) were significant factors for mean systolic BP. A two-minute rest was not a significant factor in mean BP. The differences in adjusted mean systolic BPs were significant for rest times of five minutes vs. two minutes (3.1 mmHg, p < 0.0001), for stressful stimuli (0.8 mmHg, p < 0.0001), and for survey year (127.8 ± 0.2 mmHg vs. 122.2 ± 0.3 mmHg for 2018 vs. 2019, p < 0.0001). Conclusion: For the community-based home visit survey, avoidance of stressful stimuli, five-minute rest, and allocation of BP measurement in the last part of the survey was useful for obtaining a stable BP level.